Early response to subinhibitory antibiotic exposure in Sinorhizobium meliloti - Kothe, Jennifer Anja Franziska; Justus Liebig University Giessen (My University, 2024)
The Gram-negative Alphaproteobacterium Sinorhizobium meliloti is frequently exposed to antibiotics in its natural soil habitat. In this study, transcriptome changes after 10 min of subinhibitory tetracycline (Tc) exposure were analyzed. RNA sequencing revealed 373 mRNAs with significant changes in mRNA level, with genes with the highest increase in mRNA level being rather short, and genes encoding for proteins with a domain of unknown function 1127 (duf11271 to duf11276) were overrepresented. RNA stability analysis revealed that the mRNA half-lives of several up- and down-regulated genes was increased upon Tc exposure. After initial validation, selected up-regulated genes were tested for their response to different stressors and analyzed using reporter fusions. The gene with highest mRNA increase, duf11271, responded specifically to translation inhibitors and for its regulation, the mRNA leader was crucial. In the duf11271 mRNA leader, three short upstream open reading frames were found, uORF1, uORF2, and uORF3, the latter overlapping duf11271. RNA and protein analyses revealed that uORF1 translation is necessary for transcriptional attenuation of duf11271. This operon was not regulated by intrinsic termination. A deletion analysis suggested an attenuation element, a potential, C-rich Rho utilization (rut) site downstream of uORF1. 3’ RACE revealed multiple 3’ ends downstream of this rut site, further supporting Rho-dependent transcription termination. These 3’-ends were around the start codon of uORF2, which was co-regulated with duf11271 at the level of RNA, but not at the protein level, suggesting regulation of the duf11271 translation in response to Tc. However, start to stop mutation destroying uORF2 did not influence duf11271 regulation. Translation of uORF3 could not be validated, but its Shine-Dalgarno sequence was necessary for duf11271 translation. While the translational regulation of duf11271 and the function of this gene were not deciphered, detailed mutational analysis of reporter fusions revealed an unexpected mechanism for transcription attenuation. The presented data show that the first half of uORF1 (29 aa) must be translated for duf11271 regulation. In codons 3-10 of uORF1, another attenuation element was found, which is also C-rich and C to G mutations led to de-repression of the duf11271 fusion. This supports the existence of a rut site in this region. The unexpected localization of this rut site near the beginning of uORF1 could be explained by its regulation in the absence of translation, when it is masked by base-pairing with the ribosome binding site (RBS) of uORF1. This explanation was supported by mutational and deletion analyses. Taken together, this work shows a complex regulation of duf11271 in response to Tc exposure, which includes mRNA stabilization, Rho-dependent transcription attenuation, and, possibly, translational control. The following mechanism is proposed for the duf11271 regulation by transcription attenuation: A rut site is present near the beginning of uORF1, which is only accessible upon translation. In between one ribosome translating and moving downstream, and before a new ribosome occupies the RBS of uORF1, a time window allows Rho to access the rut site and terminate transcription further downstream. Upon Tc exposure, translation initiation is impaired, and the ribosome blocks the rut site, leading to duf11271 induction. In the absence of translation, the RBS and the rut site base-pair, abolishing premature transcription termination. This new mechanism is well-suited to monitor the availability of ribosomes and translation efficiency under stress conditions and control the expression of the duf11271 gene.
Keywords: ddc:570